Sport and performance in the twenty-first century - Blair, Kelsey (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Analyzing sport through the lens of performance and theorizing performance through the lens of sport, 'Sport and Performance in the Twenty-First Century' offers a field intervention, a series of in-depth performance analyses, and an investigation of the intersection between sport performances and public life in the historical present in the global north. The objectives of this book are three-fold. First, the book advocates for the study of sport in the fields of Theatre and Performance Studies and, through in-depth performance analyses, demonstrates how the critical language and methods of performance studies help illuminate the manifold impacts of the practices, activities, and events of sport. Second, the book introduces new critical language that was originally developed in conjunction with sport but is also designed for cross-genre performance analysis. In introducing novel terminology, the book aims to simultaneously facilitate analysis of sport performances and to demonstrate how the study of sport can contribute to the fields of Theatre and Performance Studies. Finally, the book investigates the epistemological, affective, and socio-political effects of sport performances and to demonstrate how sport performances influence, and are influenced by, their historical conditions. This study will be of great interest to students and scholars in Theatre and Performance Studies, Physical Culture Studies, and Socio-Cultural Sports Studies"--
Introduction: Sport and the Field of Performance -- Performance Genres, Sport, and Match-fixing at the 2012 Olympic Games -- Configurations and Formations: The Patterning of Behaviour in Performance Activities and the Practice of Women's Basketball -- The Patterning of Audience Behaviours and Hockey in Canada -- Sequences of Action Across Genres: Injury Mini-Dramas and American Football -- Gestural Marks in Sport Performance, The Genealogy of the Butterfly, and the Refugee Olympic Team.
Keywords: Sports; Performance; PERFORMING ARTS / General; PERFORMING ARTS / Acting & Auditioning; PERFORMING ARTS / Comedy